Screening of Transformed Bacteriial Colonies By Using Polymerase Chain Reaction (Pcr-screening) - Özdarendeli, Aykut; Toraman, Zülal Aşçı; Kuk, Salih; Tonbak, Şükrü; Bulut, Yasemin; Kalkan, Ahmet (Fırat University, 2003)
Aim: In this study, it was investigated that bacterial colonies obtained after transformation were tested whether they contained positive recombinant colonies by using PCR screening method. Material and method: For this aim, Fasciola hepatica cathepsin L1 gene and Rinderpest virus matrix gene were cloned into three different vector systems and transformed into E. coli. It was determined some bacterial colonies which had the right size band after PCR screening. Plasmid DNA of those bacterial colonies was extracted by classical miniprep method. The colonies positive with PCR screening were assayed by enzyme digestion assays to verify the PCR screening results. Results: There was 100% correlation between PCR screening and enzyme digestion assays. Conclusion: Using PCR screening method reduce the time requirement for detection the positive colonies and saving the materials used for plasmid DNA extraction.

Amaç: Bu çalışmada Polimeraz Zincir Reaksiyonu Tarama (PZR-T) yöntemiyle klonlama sonucu elde edilen bakteriyel kolonilerin pozitifliği araştırılmıştır. Gereç ve yöntem: Fasciola hepatica katepsin L1 geni ve sığır vebası virüs matriks genleri üç farklı vektör sistemine klonlandıktan sonra E.coli kompetan hücrelerine transformasyon yapıldı. Transformasyon sonucu elde edilen kolonilerin bir kısmı PZR-T yöntemi kullanılarak değerlendirmeye tabi tutuldu. PZR-T sonucu istenilen büyüklükte elde edilen bantları içeren koloniler belirlenerek klasik miniprep yöntemiyle plasmid DNA'lar elde edildi. Kesim deneyleri yapılarak istenilen gen bölgelerinin varlığı doğrulandı. Bulgular: PZR-T ile pozitif olduğu saptanan 61 örneğin tamamının miniprep sonrası yapılan kesim deneylerinde de pozitif olduğu belirlendi. Sonuç: PZR-T yöntemiyle hem çok daha kısa zamanda pozitif koloniler belirlenecek hem de materyal açısından büyük ölçüde tasarruf edilmiş olacaktır.
Polimeraz Zincir Reaksiyonu ile Transforme Bakteriyel Kolonilerın Belirlenmesi (Pzr-tarama)